Bio-based coatings containing mycosporine-like amino acids (MAA) to control sunscald abiotic stress in orange fruit (Citrus sinensis L) - Pedrosa, Vanessa Maria Dantas [UNESP]; Sanches, Alex Guimarães [UNESP]; da Silva, Maryelle Barros [UNESP]; Gratão, Priscila Lupino [UNESP]; Isaac, Vera Lúcia Borges [UNESP]; Gingri, Marcelo [UNESP]; de Almeida Teixeira, Gustavo Henrique [UNESP] (Elsevier, 2024)
Oranges are susceptible to many abiotic stresses, and the fruit is particularly susceptible to sunscald, a physiological disorder caused by excessive solar radiation. Sunscald is commonly controlled by spraying the fruits with calcium hydroxide and/or kaolin, but this procedure is not always effective due to rain and the application of phytosanitary treatments. Since mycosporine-like amino acids (MAAs), produced by many marine organisms, protect them against ultraviolet radiation UV-A and UV-B, these compounds could be incorporated into bio-based emulsions to control sunscald in oranges. Therefore, increasing concentrations of the commercial product Helioguard™ 365 (0 %, 1 %, 2 %, and 4 % - v/v), a source of MAAs, were incorporated into lipid-based emulsions. The emulsions were applied during the final stage of development of ‘Hamlin’, ‘Pera-rio’, and ‘Valencia’ oranges at 21-day intervals. Spraying with 5 % (w/v) calcium hydroxide served as the positive control treatment, while untreated fruits served as the negative control. Incorporating MAA into the emulsion did not demonstrate effective control of sunburn compared to the positive control treatment with calcium hydroxide, as all fruits exhibited varying degrees of sunscald, ranging from low to high severity. Regarding physicochemical parameters, as well as oxidative metabolism, except for color parameters, soluble solids content, ascorbic acid, and overall biochemical parameters, there was no difference among treatments for any of the evaluated orange cultivars. The activities of ascorbate peroxidase (APX) and superoxide dismutase (SOD) did not show consistent with efficient antioxidant potential capable of significantly reducing the malondialdehyde (MDA) content. Despite using MAA at the evaluated concentrations and experiencing severe climatic interference in 2020, efficient control of sunscald in oranges was not achieved. Further research is needed to identify more effective alternatives and gain a better understanding of how climate affects oxidative aspects.
Keywords: Ascorbate peroxidase; Heat stress; Malondialdehyde; Oxidative metabolism; Physiological disorder; Superoxide dismutase